Densification Behaviors of Zirconium Carbide with Silicon Additive Produced by Spark Plasma Sintering - Qisen Ren; Lixiang Wu; Yang Liu; Jun Yan; Yehong Liao; Weiming Guo; Weiqiang Liu (Nuclear Materials and Energy)
Zirconium Carbide (ZrC) is a promising matrix material candidate for Fully Ceramic Microencapsulated (FCM) fuel. Using Spark Plasma Sintering (SPS) and introducing a certain amount of Si as sintering additive can effectively promote the sintering densification process, reduce the sintering temperature, and avoid adverse effects on the microstructure and properties of the matrix and fuel phase during high-temperature sintering process. Adopting SPS process, this article investigates the effects of Si addition, sintering temperature, sintering pressure, and holding time on the density and microstructure of ZrC sample. The results indicate that the sintering temperature and Si addition amount are the key factors affecting the densification of ZrC, while the sintering pressure and holding time have a relatively small impact. The addition of Si could effectively promote the densification procedure during ZrC sintering. Introducing 2.5 wt% of Si increased the maximum densification rate by more than 200 % compared to that of pure ZrC, under sintering condition of 1600 °C/20 MPa/10 min.